Physicochemical study of ascorbic acid 2-glucoside loaded hyaluronic acid dissolving microneedles irradiated by electron beam and gamma ray. (15th January 2018) - Kim, Suyong; Lee, Jeongwon; Shayan, F. Lahiji; Kim, Seohyun; Huh, Inyoung; Ma, Yonghao; Yang, Huisuk; Kang, Geonwoo; Jung, Hyungil
Highlights: Hyaluronic acid-based dissolving microneedles were fabricated and sterilized. Electron beam (e-beam) and gamma ray (γ-ray) were used for sterilization. Irradiation did not affect morphology and fracture force of dissolving microneedles. E-beam and γ-ray reduced microorganismal contamination; γ-ray degraded the drug. Hyaluronic acid stabilizes and can inhibit degradation of the encapsulated drug. Abstract: A dissolving microneedle (DMN) patch encapsulated with ascorbic acid 2-glucoside (AA2G) in a needle-shaped hyaluronic acid (HA) backbone was fabricated and sterilized by electron beam (e-beam, 5–40 kGy) and gamma ray (γ-ray, 5–30 kGy). DMN structures maintained their morphologies and fracture force regardless of e-beam and γ-ray irradiation doses. Both e-beam (40 kGy) and γ-ray (20 and 30 kGy) met the product sterility requirements for cosmetics and vaccines; however, γ-ray irradiation significantly degraded the encapsulated AA2G, while e-beam maintained AA2G activity. Thus, an e-beam dose of 40 kGy, which satisfied the sterility requirements without loss of AA2G, is suitable for terminal sterilization of DMNs. Moreover, we confirmed that the optimized irradiation (e-beam, 40 kGy) did not affect dissolution rate and drug release profile of DMNs. Further, we confirmed that HA, the backbone polymer of DMNs, could be utilized as a stabilizer that inhibits degradation of encapsulated AA2G by irradiation. This detailed analysis can be developed further to optimize various biological drugs in transdermal drug delivery systems.